2019
DOI: 10.1088/1361-6668/aaf61a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Mg doping on the microstructure and transport properties of internal tin-processed brass matrix Nb3Sn superconductors

Abstract: The addition of Zn into Cu matrix has been proved to enhance the Sn activity and accelerate the formation of a Nb3Sn layer in internal tin-processed Nb3Sn wires. However, in our samples, Ti is doped in Sn cores, and during the reaction, Ti was observed to accumulate between the inner and outer sub-elements of the 1980-Nb-core multi-filamentary brass matrix wires. With the addition of Mg into the brass matrix, Ti accumulation between the sub-elements was significantly suppressed, which promoted Ti incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For either low T c or high T c a number of works have attempted to discover the origin of the peak effect in the magnetization. Depending on the particular system investigated, the origin has been found to have an association with different processes [25][26][27][28][29]. In order to shed light on the pinning mechanisms in the field region of the SMP in our samples, we studied the magnetic field dependence of the pinning force density F p .…”
Section: Resultsmentioning
confidence: 99%
“…For either low T c or high T c a number of works have attempted to discover the origin of the peak effect in the magnetization. Depending on the particular system investigated, the origin has been found to have an association with different processes [25][26][27][28][29]. In order to shed light on the pinning mechanisms in the field region of the SMP in our samples, we studied the magnetic field dependence of the pinning force density F p .…”
Section: Resultsmentioning
confidence: 99%
“…The data for 650 is the value just after the pre annealing. The holding time for the nal heat treatment is 100 h26 .…”
mentioning
confidence: 99%
“…Our laboratory samples had larger Nb barrier thicknesses compared with practical internal tin Nb 3 Sn strands. Therefore, when the non-Cu J c was calculated, we used an equivalent area fraction of the barrier in the non-Cu region, which was set as 10% with a slight overestimation, referring to that of typical practical internal tin Nb 3 Sn strands (6%-8%) [35,59].…”
Section: J C Measurementmentioning
confidence: 99%
“…Higher Sn activity should also promote nucleation of the Nb 3 Sn phase at the Nb/Nb 3 Sn interface. We have also recently demonstrated that co-doping of Zn and a small amount of Mg to the matrix leads to finer grain morphologies and better J c performances [35]. In early works, Mg was also reported as an effective additive to increase the layer growth rate [36], reduce the grain size [36,37], and improve the J c performance [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%